Protective Effect of a Synthetic Polynucleotide Complex (Poly I: C) on Ocular Lesions Produced by Trachoma Agent in Rabbits - Oh, J. O. (1970)
Live trachoma agent (TE55) injected into the anterior chamber of the rabbit eye produced the following agent-specific ocular lesions: corneal opacity, corneal neovascularization, and iritis. Three intravenous injections of 1 mg of a potent interferon (IF) inducer, polyriboinosinic acid-polyribocytidylic acid complex (poly I:C), markedly suppressed the ocular lesions produced by the trachoma agent but failed to inhibit the growth of the agent in the ocular tissues. Furthermore, a single intravenous injection of 1 mg of polyriboinosinic acid or of polyribocytidylic acid was also protective, although each failed to induce any detectable circulating IF. These results indicate that a factor or factors other than IF may play a role in the suppression of the ocular lesions produced by trachoma agent in poly I:C-injected rabbits.